Propuesta de centro parroquial y puesta en valor de la iglesia Santo Domingo de Guzmán para el distrito de Chicama, La Libertad, 2022 - Hilario Santos, Rosa Jackeline (2023)
Chicama Valley was part of evangelization process after the spanish_x000D_ arrival. Introducing the need of religiosity and concentrating in an old_x000D_ church which actually it represents an identity symbol for Chicama's_x000D_ people, and it's still preserves cultural values despite being in a_x000D_ precarious state due to its abandonment. In order to elaborate the_x000D_ project, on-site and desktop investigations were carried out, while_x000D_ consulting relevant local, national and international regulations. Such_x000D_ needs found in the analysis, gave rise to the present architectural project_x000D_ whose objective is to improve the deficient infrastructure and at the_x000D_ same time, to value that historical monument, because it's at risk of_x000D_ getting lost.The project is strongly supported by three pillars, such as:_x000D_ Strengthen the identity of Chicama town; also being an inclusive_x000D_ project, where no one is left out or feels strange when stepping on the_x000D_ facilities; and at the same time it is sustainable, with technological_x000D_ characteristics that are friendly to the environment. The symbiosis is_x000D_ present in the project, since it brings together the religious, cultural,_x000D_ social, and even educational aspects to be developed, in a balanced_x000D_ way, and developed on abundant nature.